Physical activity, fruit and vegetable intake, and incidence of type 2 diabetes mellitus: a case-control study - Gebang, Antonius Adolf; Kusnanto, Hari; Huriyati, Emy (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to analyze the relationship between factors of physical activity and fruit and vegetable intake with the incidence of type 2 diabetes mellitus in Temanggung District. Methods: This study employed an observational analytic design using an incidence density case-control study, with a 1:1 comparison of cases and controls, without matching. Research data retrieval is based on the health center surveillance report and direct interviews with respondents. This research was conducted in 10 health centers located in the Temanggung Regency area of ​​Central Java Province, which had a higher incidence of cases. The sample in this study consisted of 150 respondents, divided into 75 case respondents and 75 control respondents. Results: The results of bivariate analysis showed that there was a relationship between age factors, family history (OR: 2.13; 95% CI: 1.05-4.31; p-value=0.02), obesity (OR: 2.15; 95% CI: 0.99-4.69; p-value=0.03), physical activity and eating fruit vegetables (OR: 5.02; 95% CI: 2.35-10.84; p-value=0.00) with the incidence of type 2 diabetes mellitus while the sex and occupational factors had no association with the incidence of type 2 diabetes mellitus. The multivariate analysis revealed a relationship between family history, physical activity, and fruit and vegetable intake, as well as the incidence of type 2 diabetes mellitus, in the final model. Conclusion: Low physical activity and a diet low in vegetables can increase the risk of developing type 2 diabetes mellitus. Intensive and routine counseling is necessary to increase community knowledge and establish more health services, such as Posbindu, in each village to maximize the early detection of diabetes mellitus.